The Black Lives Matter Movement Affected the View About Racism in the World - Toshbekov, Bobur Bakhrom ugli (International Journal of Law and Society, 2022)
This research aims to explain the black lives matter movement and and how this movement can influence views on racism. This research uses mixed methods, quantitative and qualitative. The study demonstrates that public interest in the BLM plan is fast-growing, even though media and social media data are used to verify BLM protests. While the protests are over, BLM and related issues will be discussed. The acts are likely to have influenced BLM's ideas on social change and grasp of anti-racist ideologies. Because of the Black Lives Movement, racism has changed significantly. Racism has had a significant impact on modern society because it has drawn attention and made people more aware of the fundamental nature of racism. One can't say how many discriminatory acts it has stopped, but it's possible. But it has looked into all of the discriminatory actions that have gone unanswered for a long time now.